Discover a wealth of knowledge at Westonci.ca, where experts provide answers to your most pressing questions. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.

Solve for k in the equation 12 = 4(k - 6)

Sagot :

Answer:

12 = 4 (k - 6) (use the distributive property to get rid of the parentheses)

12 = 4k -24 (add 24 to both sides to isolate the k-term)

36 = 4k (divide both sides by 4 to get k all alone)

k = 9 (your answer)

Step-by-step explanation:

I hope this helped :))